Optimization of the soda-ethanol delignification stage for a rice husk biorefinery - Dagnino, Eliana Paola; Felissia, Fernando E.; Chamorro, Ester Ramona; Area, María Cristina (My University, 2017)
The aim of this work was to optimize the delignification of the hemicelluloses-free fraction of rice husk to obtain fractions of lignin, cellulose, and inorganics, which could be valorized in the context of the rice husk biorefinery. The hemicelluloses were pre-extracted from the raw material by dilute sulfuric acid, and a soda-ethanol-water process was used for delignification. Two experimental designs were carried out to evaluate different ranges of the same variables (strong and light conditions), aiming to promote maximal delignification or delignify while protecting carbohydrates. The optimal delignification points were obtained using 13 and 8% of NaOH (%w/w on solid material), in a 50:50 and 54:46 ethanol:water solution. In these conditions, 94.3 and 90.1% of lignin and almost 100 and 40% of inorganics were removed from the solid, respectively. The used soda-ethanol-water process can be defined as a soda process additivated with ethanol, showing significant advantages over soda-anthraquinone process for the fractionation of lignocellulosic materials.
Keywords: biorefinery rice huskK; soda-ethanol-water process; delignification optimization